Implementasi Pembelajaran Karakter Religius Siswa SDIT Alam Bina Insani Melalui E-Book Cerita - Fatwa, Alyan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Process of instilling character values in elementary school, one must look at the stages of child development and right method. The methods used by teachers to instill character values in students at SDIT Alam Bina Insani is through storytelling. This study aims to describe application of story method in learning to instill character values in SDIT Alam Bina Insani students. describe supporting and inhibiting factors. This type of research is field research, with a descriptive qualitative approach. Collecting data with interview techniques, observation, and documentation. The results of this study indicate that the application of story method in learning to instillcharacter values of students at SDIT Alam Bina Insani, namely habit of praying before starting and ending learning, the habit of saying toyyibah sentences when listening to amazing or terrible stories, practicing or reciting direct readings and prayers.The prayers contained in story, as well as emulating commendable attitudes of pious figures. Factors supporting application of story method are sufficient learning resources and media, the teacher's ability to tell stories in an interesting way, comfortable classroom conditions and environments. While inhibiting factors are limited time in telling stories, fast-changing concentration of children, and different learning styles of students.